Police Intervention in Corruption Prevention: Police and Community Synergy in Improving the Anti-Corruption Character of Students at Tlogodepok Mirit Kebumen - Surip Surip; Ridwan Arifin; Anis Widyawati; Rasdi Rasdi; Septhian Eka Adiyatma (Advances in Police Science Research Journal, 2021)
.